Application of a dispersive micro‐solid‐phase extraction method for pre‐concentration and ultra‐trace determination of cadmium ions in water and biological samples. (9th November 2017) - Behbahani, Mohammad; Veisi, Ali; Omidi, Fariborz; Noghrehabadi, Aminreza; Esrafili, Ali; Ebrahimi, Mohammad Hossein
Abstract : A method for the trace determination of cadmium ions in water, human urine and human blood serum samples using ultrasonic‐assisted dispersive micro‐solid‐phase extraction (UA‐D‐μSPE) was developed. Silica‐coated magnetic nanoparticles were coated with polythiophene, and the resulting sorbent was characterized using thermogravimetry, differential thermal analysis, scanning electron microscopy, Fourier transform infrared spectrometry and X‐ray diffraction. Following UA‐D‐μSPE, cadmium ions were quantified using graphite furnace atomic absorption spectrometry. A Box–Behnken design was used for optimization of important sorption and desorption parameters in UA‐D‐μSPE: in the sorption step, pH of solution, sorption amount and sonication time for sorption; in the desorption step, concentration of eluent, volume of eluent and sonication time. The optimum conditions for the method were: pH of solution, 7.5; sonication time for sorption, 3 min; sorption amount, 35 mg; type and concentration of eluent, HCl and 1.1 mol l −1 ; volume of eluent, 360 μl; sonication time for desorption, 110 s. Under the optimized conditions the limit of detection and relative standard deviation for the detection of cadmium ions by UA‐D‐μSPE were found to be 0.8 ng l −1 and <6%, respectively. Abstract : A method for the trace determination of Cd(II) in water, human urine and human blood serum samples using ultrasonic‐assisted dispersive micro‐solid‐phase extraction (UA‐D‐μSPE) was developed. Under the optimized conditions the limit of detection and relative standard deviation for the detection of cadmium ions using UA‐D‐μSPE was found to be 0.8 ng l −1 and <6%, respectively.